Heroism of suicide in stoicism and early Oyo empire traditional political setting (2014)
Suicide, as a concept, has been a subject of philosophical, psychological, sociological and religious inquiry in ancient, medieval and modem history of ideas. 'Through the course of history, suicide has evoked a wide range of reactions. It has been both condemned and condoned by various societies. Generally, suicide is regarded as an anti-social behaviour, condemned by Christianity, Islam and Traditional Religions. Despite the condemnation, suicide was still condoned under certain circumstances. For instance, in ancient Greece and in the early Oyo Yoruba political setting, suicide was an acceptable way of dealing with military- defeat in order to preserve national and personal honour and dignity. Therefore, a number of questions such as what have constituted suicide?’ ‘ to what extent can suicide be- considered a rational choice?’ ‘And what is the moral permissibility of suicide?’ have been raised. Philosophical arguments, regarding whether or not suicide can be morally acceptable, range from strong opposition to its perception as a sacrosanct right. The latter is a strong tenet of the Stoics who consider suicide as an honorific act. Although thee Yoruba condemn suicide, they also condone and even consider it an honourable thing to do under certain circumstances. ’This paper examines the honourable aspects of Stoics’ concepts of suicide and the politically motivated suicide in the early Oyo Empire traditional political organization such as the case where a host of title holders, known as abobaku, had to commit suicide at the demise of the king so as to accompany him to the hereafter. Today, however, many commit suicide not out of traditional obligation but to escape what seem to be unbearable circumstances claiming that suicide is a personal choice. This paper argues that no matter how plausible the idea is suicide is inadmissible and abominable from every standpoint